A fat-derived metabolite regulates a peptidergic feeding circuit in Drosophila. - Kim, D.H.; Shin, M.; Jung, S.H.; Kim, Y.J.; Jones, W.D. (PLoS Biology, 2017)
Here, we show that the enzymatic cofactor tetrahydrobiopterin (BH4) inhibits feeding in Drosophila. BH4 biosynthesis requires the sequential action of the conserved enzymes Punch, Purple, and Sepiapterin Reductase (Sptr). Although we observe increased feeding upon loss of Punch and Purple in the adult fat body, loss of Sptr must occur in the brain. We found Sptr expression is required in four adult neurons that express neuropeptide F (NPF), the fly homologue of the vertebrate appetite regulator neuropeptide Y (NPY). As expected, feeding flies BH4 rescues the loss of Punch and Purple in the fat body and the loss of Sptr in NPF neurons. Mechanistically, we found BH4 deficiency reduces NPF staining, likely by promoting its release, while excess BH4 increases NPF accumulation without altering its expression. We thus show that, because of its physically distributed biosynthesis, BH4 acts as a fat-derived signal that induces satiety by inhibiting the activity of the NPF neurons.